2021
DOI: 10.3390/ani11082153
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue- and Bone Marrow-Derived Mesenchymal Stem Cells from Sheep: Culture Characteristics

Abstract: The current study demonstrates the culture characteristics of adipose tissue and bone marrow-derived mesenchymal stem cells (MSC). The study evaluates the effect of ambient temperature, physiological status of the donor and the tissue source on sheep (Ovis aries) mesenchymal stem cells. The tissue samples were harvested from full term pregnant female sheep (n = 9) and male sheep (n = 10). Adipose tissue was harvested from n = 9 sheep and bone marrow from n = 10 sheep. The samples (adipose tissue, n = 2; bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 2021 ; Dar et al. 2021 ). The mononuclear cell (MNC) fraction harvested contains MSCs that are culture expanded.…”
Section: Why Stromal Vascular Fraction?mentioning
confidence: 99%
See 2 more Smart Citations
“… 2021 ; Dar et al. 2021 ). The mononuclear cell (MNC) fraction harvested contains MSCs that are culture expanded.…”
Section: Why Stromal Vascular Fraction?mentioning
confidence: 99%
“…2016 ; Dar et al. 2021 ). One of the studies demonstrated that AdSVF composes mainly of AdMSCs (15–30%) along with other cellular components like immune cells (25–45%), endothelial cells (10–20%), and pericytes (3–5%) (Bourin et al., 2013).…”
Section: Composition Of Stromal Vascular Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the immunophenotypic landscapes of ovine MSCs are similar to human MSCs, most antibodies reacting with human MSCs did not exhibit the reactivity with the surface antigens of ovine MSCs. The investigations performed by Dar et al (2021) have shown that ovine BM-and ATderived MSCs are simultaneously characterized by the increased expression levels recognized for CD73 and CD90 markers, and the absence of CD34 and CD45 antigens. Other studies undertaken to identify the immunophenotypic landscapes specific for ovine BM-MSCs have confirmed the high expression of CD29, CD166 and CD44 antigens and the lack of expression of the CD45 marker (Sanjurjo-Rodríguez et al, 2017).…”
Section: Immunophenotypic Cytobiochemical Cytophysiological and Molec...mentioning
confidence: 99%
“…[134]. Indeed, many factors, such as the storage temperature of the MSCs and preservation agents employed, could also affect the effectiveness of this cell therapy [135,136]. For these reasons, we are still far from knowing the most optimal conditions for the use of MSCs as a therapeutic tool in preclinical and clinical trials in OA [137,138].…”
Section: Mesenchymal Stem Cell Therapy Targeting Osteoclastmentioning
confidence: 99%